Performance of the psychosocial sector at SEMEC in the Municipality of Abaetetuba/PA – Approaches and challenges - Almeida, Kelly Samara dos Santos; Ferreira, José Lúcio Negrão; Costa, Regiane Barreto da; Cardoso, Maria do Socorro Costa (Seven Editora, 2023)
The article deals with the performance of the psychosocial sector in education as a multiprofessional segment (Social Workers, Psychologists and Educational Advisors) that intervenes in the expressions of the “social issue” arising from the school space. With the objective of establishing reflections on performance, challenges and interventions in the educational service, documentary and bibliographic research were carried out, based on the theoretical-methodological assumptions of Dialectical Historical Materialism with emphasis on education policy as a social right, whose result points to a possible and necessary insertion of this multiprofessional team in the educational reality in the municipality with a view to guaranteeing the right to education and its teaching-learning process with quality. DOI:https://doi.org/10.56238/interdiinovationscrese-049